Case report: Laparoscopic gastrojejunostomy for duodenal atresia with situs inversus and preduodenal portal vein: a report of two cases - Nakagawa, Yoichi; Sumida, Wataru; Makita, Satoshi; Uchida, Hiroo; Hinoki, Akinari; Shirota, Chiyoe; Tainaka, Takahisa; Yokota, Kazuki; Amano, Hizuru; Yasui, Akihiro; Takimoto, Aitaro; Kato, Daiki; et al. (Frontiers in Pediatrics, 2023)
Congenital duodenal atresia with situs inversus is occasionally accompanied by a preduodenal portal vein (PDPV), which is incidentally diagnosed during surgery. Duodenoduodenostomy is the most common and effective treatment. However, some patients require other anastomoses. Here, we present two cases of laparoscopic gastrojejunostomy for congenital duodenal atresia with situs inversus and PDPV and describe the reason for selecting gastrojejunostomy. The optimal surgical strategy is patient specific and should be determined based on the patient’s general and physical condition.